Against Strong Ethical Parity: Situated Cognition Theses and Transcranial Brain Stimulation - Heinrichs, Jan-Hendrik (Frontiers in Human Neuroscience, 2017)
According to a prominent suggestion in the ethics of transcranial neurostimulation the effects of such devices can be treated as ethically on par with established, pre-neurotechnological alterations of the mind. This parity allegedly is supported by situated cognition theories showing how external devices can be part of a cognitive system. This article will evaluate this suggestion. It will reject the claim, that situated cognition theories support ethical parity. It will however point out another reason, why external carriers or modifications of the mental might come to be considered ethically on par with internal carriers. Section 1 presents the ethical parity theses between external and internal carriers of the mind as well as neurotechnological alterations and established alterations. Section 2 will elaborate the different situated cognition approaches and their relevance for ethics. It will evaluate, whether transcranial stimulation technologies are plausible candidates for situated cognition theses. Section 3 will discuss criteria for evaluating whether a cognitive tool is deeply embedded with a cognitive system and apply these criteria to transcranial brain stimulation technologies. Finally it will discuss the role diverse versions of situated cognition theory can play in the ethics of altering mental states, especially the ethics of transcranial brain stimulation technologies.